KONSTRUKSI MAKNA PROFESI JURNALIS BAGI JURNALIS PEREMPUAN DI KOTA PEKANBARU - Aulya, Suci; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
As the time goes, nowadays the profession that usually did by a male also did by female too such journalist on the field. In Pekanbaru City, the number of female journalist are not comparable with the number of male journalist. Eventhough they are not comparable, there are still female who engaged to do this profession and persist for decades. This research aims to determine the motive of meanings and communications experience of female journalist in Pekanbaru City.This research is a qualitative research with phenomenology approach. The informant of this research are the female journalist in Pekanbaru with six persons that has been choosen with purposive technique. The data was collected through interviews, observation and documentations. The data analysis technique includes data reduction, data presentation and conclusion and verification.The result of this research shows that first, the motive of female did this journalist profession in Pekanbaru City consist of because motive like writting hoby, coriosity of the unethical journalist, likes to work for field, admiring the journalist profession and want to tell informations to people. While in order to motive is to improve performance, to bring back journalist profession to the right plot, developing the local media and stop becoming a journalist. Second, meaningness that given by female journalist to journalist profession is voicing struggles, the profession doesn’t time, the challenging profession, free profession. Third, communication experience that divided into two categories such as fun communication experience that got positivies respond and interviewees, intertwined relationship that closely with friends and support from family. While not fun communication experience such as irrevent treatment from male interviewees, less adressed, and got negatives critical from interviewees, have to follow the male journalist rhythm, late night coverage, risking coverage, and not get support from family.Keyword: construction of meaning, journalist profession, female journalist, motive, meaning, communication experience